Deficient immune response following SARS-CoV-2 vaccination in patients with hepatobiliary carcinoma: a forgotten, vulnerable group of patients? - Malte Benedikt Monin; Leona I. Baier; Jens G. Gorny; Moritz Berger; Taotao Zhou; Robert Mahn; Farsaneh Sadeghlar; Christian Möhring; Christoph Boesecke; Kathrin van Bremen; Jürgen K. Rockstroh; Christian P. Strassburg; et al. (Liver Cancer, 2023)
Background: Data on immune response rates following vaccination for SARS-CoV-2 in patients with hepatobiliary carcinoma (HBC) are rare. However, impaired immunogenicity must be expected due to the combination of chronic liver diseases (CLD) with malignancy and anticancer treatment. Methods: In this prospective, longitudinal study, 101 patients were included, of whom 59 were patients with HBC under anticancer treatment. A cohort of patients with a past medical history of gastrointestinal cancer (GI-cancer), of whom 28.6% had HBC without detectable active tumor disease having been off therapy for at least 12 months served as control. Levels of SARS-CoV-2 anti-spike IgG, surrogate neutralization antibodies (sNAB) and cellular immune responses were compared. In uni- and multivariable subgroup analyses, risk factors for impaired immunogenicity were regarded. Data on rates and clinical courses of SARS-CoV-2 infections were documented. Results: In patients with HBC under active treatment, levels of SARS-CoV-2 anti-spike IgG were significantly lower (2.55 log10 BAU/mL; 95% CI 2.33 to 2.76; p<0.01) than in patients in follow-up care (3.02 log10 BAU/mL; 95% CI 2.80 to 3.25) four weeks after two vaccinations. Antibody levels decreased over time and differences between the groups diminished. However, titers of SARS-CoV-2 sNAB were for a longer time significantly lower in patients with HBC under treatment (64.19%; 95% CI 55.90 to 72.48; p<0.01) than in patients in follow-up care (84.13%; 95% CI 76.95 to 91.31). Underlying chronic liver disease (CLD) and/ or liver cirrhosis Child Pugh A or B (less than 8 points) did not seem to further impair immunogenicity. Conversely, chemotherapy and additional immunosuppression were found to significantly reduce antibody levels. After a third booster vaccination for SARS-CoV-2, levels of total and neutralization antibodies were equalized between the groups. Moreover, cellular response rates were balanced. Clinically, infection rates with SARS-CoV-2 were low and no severe courses were observed. Conclusions: Patients with active HBC showed significantly impaired immune response rates to basic vaccinations for SARS-CoV-2, especially under chemotherapy, independent of underlying cirrhotic or non-cirrhotic CLD. Although booster vaccinations balanced differences, waning immunity was observed over time and should be monitored for further recommendations. Our data help clinicians to decide on individual additional booster vaccinations and/ or passive immunization or antiviral treatment in patients with HBC getting infected with SARS-CoV-2.